Pengembangan Bahan Ajar IPS pada Materi Keragaman Suku Bangsa dan Budaya Dengan Menggunakan Metode Storytelling di Kelas IV SD - Elda Nabilla; Tiflatul Husna (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to produce social studies teaching materials that can attract students' attention to the subject of Ethnic and Cultural Diversity using the storytelling method in class IV SDS IT Zahra Asy Syifa. This research is a Research and Development (R&D) development study using the ADDIE development procedure which consists of 5 stages. The instrument used to collect data was a validation questionnaire given to several expert validators, namely the material expert validator, teaching material expert validator and teacher response. The total score obtained from the validation of teaching materials was 97.6 with the criteria of